2D Side‐Chain Engineered Asymmetric Acceptors Enabling Over 14% Efficiency and 75% Fill Factor Stable Organic Solar Cells. (20th September 2020) - Cao, Jinru; Wang, Hongtao; Qu, Shenya; Yu, Jiangsheng; Yang, Linqiang; Zhang, Zhuohan; Du, Fuqiang; Tang, Weihua
Abstract: The charge transport and morphology of active layers are key considerations for device performance and stability in organic solar cells (OSCs). Such properties can be fine‐tuned via elaborate molecular design of fused‐ring electron acceptors (FREAs), especially conjugation extension and side chain engineering. In this work, N ‐functionalized conjugation is explored in the design of high‐efficient asymmetric FREAs. The twisting of N‐conjugated side chains from backbone endows three FREAs with similar energy levels and light absorptions (≈850 nm edge). Their blends with PBDB‐T exhibit high charge carrier mobility and ordered phase separation. Excitingly, IPT2F‐TT based OSCs yield a champion power conversion efficiency (PCE) of 14.02% with a fill factor (FF) of 75.06%, outperforming PBDB‐T devices with IPT2F‐Th (12.52%, 71.20%), IPT2F‐Ph (13.13%, 72.11%), and octylated IPT‐2F (13.70%, 71.50%). The PCE over 14% and FF over 75% are among the highest values for 2D FREAs OSCs reported to date. More importantly, outstanding thermal stability and light soaking stability are observed with PCE over 12% maintained after thermal or light aging for 100 h. This work demonstrates N ‐conjugated FREAs design as an effective strategy to simultaneously improve the photovoltaic performance and device stability for the OSCs. Abstract : N ‐functionalized conjugation engineering is explored for the design of 2D asymmetric nonfullerene acceptors (NFAs). Endowed with high charge transport and good nanofibrous phase separation with PBDB‐T, the best‐performing NFA contributes a champion power conversion efficiency of 14.02% in solar cells. Excellent thermal aging and light soaking stability are observed for the corresponding solar cells.